Exploring Local Ingredients Of Traditional Snacks In Solo: Culinary Heritage And Sustainable Gastronomy Identity - Hastiningsih, Wahyu Tri (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2025)
As part of the preservation of local gastronomic identity, this study investigates the use of non-wheat local food ingredients in traditional market snack products in Solo City. This research is based on the decline in the interest of the younger generation in traditional foods and the increasing dependence of the community on imported foodstuffs, especially wheat flour. By optimizing local foodstuffs, this research is expected to increase the cultural, economic, and sustainable value of food. This study uses a descriptive qualitative approach with direct observation methods, in-depth interviews, and visual documentation of market snack traders in Pasar Gede, Klewer Market, and Nusukan Market. The data obtained was analyzed through data reduction, data presentation, and thematic conclusion drawing to find patterns of local food utilization in each market snack product studied. According to the results of the study, most of the traditional Solo market snacks still use local ingredients such as rice, sticky rice, cassava, bananas, and coconut. Products such as carang gesing, gethuk lindri, and jadah blondo are real examples of preserving local food that is valuable economically, culturally, and nutritionally. However, the main problems faced include declining interest in the younger generation, lack of innovation, and lack of approach to promoting digital. In summary, local food plays an important role in strengthening Solo's culinary identity and supporting the sustainability of traditional foods. It is hoped that this research will help develop culinary innovations based on local ingredients and encourage further research that looks at nutritional value, culinary branding, and digitalization strategies of traditional market snacks.